2022
DOI: 10.1007/s00011-022-01596-w
|View full text |Cite
|
Sign up to set email alerts
|

The role of IL-1 family of cytokines and receptors in pathogenesis of COVID-19

Abstract: A global pandemic has erupted as a result of the new brand coronavirus, severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2). This pandemic has been consociated with widespread mortality worldwide. The antiviral immune response is an imperative factor in confronting the recent coronavirus disease 2019 (COVID-19) infections. Meantime, cytokines recognize as crucial components in guiding the appropriate immune pathways in the restraining and eradication of the virus. Moreover, SARS-CoV-2 can induce uncon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
35
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 38 publications
(39 citation statements)
references
References 234 publications
3
35
1
Order By: Relevance
“…In the HIV-negative setting, silymarin treatment showed trends towards suppressing pro-inflammatory cytokines from non-activated and pathogen-associated molecular pattern (PAMP)-activated primary human monocytes, and non-activated and cytokine- and T cell receptor (TCR)-activated mucosal-associated invariant T (MAIT) cells. In vitro Meroni, Barcellini, Borghi, Vismara, Ferraro, Ciani, Zanussi [11] Lymphocyte Blastogenesis Silybin,0.5, 10, and 25 μM silybin on activating human T lymphocytes and observed that silybin significantly reduce the proliferative reaction to the monoclonal anti-CD3 antibody in a dose-dependent manner In vitro Hawke, Schrieber, Soule, Wen, Smith, Reddy, Wahed, Belle, Afdhal, Navarro, Berman, Liu, Doo, Fried [12] 32 patients with chronic HCV infection Silymarin, 140, 280, 560, or 700 mg clinically meaningful reductions from baseline serum transaminases or HCV RNA titer were observed. Case report Payer et al, 2010 13 A case of an HIV-HCV coinfected patient Administration of silibinin: 20 mg/kg/day for 14 days intravenously Inhibition of HIV replication; a decrease in HCV RNA and HIV RNA Clinical trial Yakoot et al [14] 66 patients with chronic HCV infection Administration of silymarin: 140 mg 3 times daily for 6 months No virological response in the 96.6 % of silymarin treated group Clinical trial Biermer et al [15] 20 patients with chronic HCV Administration of silibinin: 1400 mg daily, infusion on 2 consecutive days Complete viral suppression in 13 of 20 patients; remaining HCV RNA negative during the subsequent follow up period Clinical trial Adeyemo et al [16] 32 patients with chronic HCV Administration of silymarin: 420 mg 3 times daily and 700 mg 3 times daily for 20 weeks No alteration in serum ALT and HCV RNA titers; suppression of C. albicans-induced T-cell IFNγ and phytohemagglutinin-induced T-cell proliferation; modest non-specific immunomodulatory effects in vivo by silymarin administration COVID-19 related article Molecular docking analysis Latha et al [17] Phytochemicals from the medicinal plants Docking analysis Better binding affinity to the target proteins of SARS-COV-2 than the synthetic repurposed drugs for treatment ...…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the HIV-negative setting, silymarin treatment showed trends towards suppressing pro-inflammatory cytokines from non-activated and pathogen-associated molecular pattern (PAMP)-activated primary human monocytes, and non-activated and cytokine- and T cell receptor (TCR)-activated mucosal-associated invariant T (MAIT) cells. In vitro Meroni, Barcellini, Borghi, Vismara, Ferraro, Ciani, Zanussi [11] Lymphocyte Blastogenesis Silybin,0.5, 10, and 25 μM silybin on activating human T lymphocytes and observed that silybin significantly reduce the proliferative reaction to the monoclonal anti-CD3 antibody in a dose-dependent manner In vitro Hawke, Schrieber, Soule, Wen, Smith, Reddy, Wahed, Belle, Afdhal, Navarro, Berman, Liu, Doo, Fried [12] 32 patients with chronic HCV infection Silymarin, 140, 280, 560, or 700 mg clinically meaningful reductions from baseline serum transaminases or HCV RNA titer were observed. Case report Payer et al, 2010 13 A case of an HIV-HCV coinfected patient Administration of silibinin: 20 mg/kg/day for 14 days intravenously Inhibition of HIV replication; a decrease in HCV RNA and HIV RNA Clinical trial Yakoot et al [14] 66 patients with chronic HCV infection Administration of silymarin: 140 mg 3 times daily for 6 months No virological response in the 96.6 % of silymarin treated group Clinical trial Biermer et al [15] 20 patients with chronic HCV Administration of silibinin: 1400 mg daily, infusion on 2 consecutive days Complete viral suppression in 13 of 20 patients; remaining HCV RNA negative during the subsequent follow up period Clinical trial Adeyemo et al [16] 32 patients with chronic HCV Administration of silymarin: 420 mg 3 times daily and 700 mg 3 times daily for 20 weeks No alteration in serum ALT and HCV RNA titers; suppression of C. albicans-induced T-cell IFNγ and phytohemagglutinin-induced T-cell proliferation; modest non-specific immunomodulatory effects in vivo by silymarin administration COVID-19 related article Molecular docking analysis Latha et al [17] Phytochemicals from the medicinal plants Docking analysis Better binding affinity to the target proteins of SARS-COV-2 than the synthetic repurposed drugs for treatment ...…”
Section: Resultsmentioning
confidence: 99%
“…Though the exact pathophysiology of COVID-19 is not fully understood so far, studies have shown that the clinical course of COVID-19 can be classified into three stages: initial viral infection, pulmonary stage, and hyper-inflammation stage ( Fig. 1 ) [11] , [12] . It is assumed that the cytokine storm and hypercoagulation of the hyper-inflammation phase contribute to disease severity and mortality [13] .…”
Section: Introductionmentioning
confidence: 99%
“…The first trial drug, astegolimab, targets the IL-33 pathway. IL-33 is an IL-1 family cytokine that functions as an alarmin, released from endothelial and epithelial tissues in response to damage from pathogens, irritants, and allergens (3, 4). It binds to the suppression of tumorigenicity 2 (ST2) receptor (also called IL-1 receptor-like 1) in target tissues and functions via both the innate and adaptive immune systems (3, 4).…”
mentioning
confidence: 99%
“…IL-33 is an IL-1 family cytokine that functions as an alarmin, released from endothelial and epithelial tissues in response to damage from pathogens, irritants, and allergens (3, 4). It binds to the suppression of tumorigenicity 2 (ST2) receptor (also called IL-1 receptor-like 1) in target tissues and functions via both the innate and adaptive immune systems (3, 4). It has been associated with inflammatory conditions including asthma and chronic obstructive pulmonary disease, and blocking this pathway may improve outcomes in asthma (5).…”
mentioning
confidence: 99%
See 1 more Smart Citation